Processo de conversão de substrato renovável por aspergillus terreus UCP 0076 na biossíntese do inibidor da HMG-CoA redutase e intermediários. - Lins, Uiara Maria de Barros Lira (2021)
HMG-CoA reductase (3-hydroxy-3-methylglutaryl-coenzyme reductase) is the enzyme that has a limiting role in cholesterol biosynthesis. Among the HMG-CoA reductase inhibitory molecules, statins stand out, such as simvastatin, a semi-synthetic drug used to reduce high cholesterol levels, being one of the most sold statins in the world. Currently, the industrial production of simvastatin occurs in a process consisting of several stages, starting from the natural product lovastatin. Studies were carried out with the objective of evaluating the biotechnological potential of Aspergillus terreus UCP0076 in the production of HMG-CoA reductase inhibitors and intermediates by submerged fermentation (FS), using agro-industrial substrate, through innovative processes. The first invention corresponded to the submerged fermentation process, using the culture media RCMS (solid cassava husk residue) and RCMC (cassava husk residue broth) consisting of cassava husks as a renewable raw material. The second refers to the development of a solid (RCMS) and liquid (RCMC) culture medium, the base of the waste disposal of cassava husks (Manihot esculenta), which provides high availability of nutrients that favor the growth of filamentous fungi and secondary metabolite production. At the end of fermentation, the product obtained corresponded to a biomolecule with a structure similar to simvastatin, corresponding to the production of 112.82 µg/mL of HMG-CoA reductase inhibitors (simvastatin), in the medium containing 4.5g of cassava peels, temperature at 28° C, pH 6.5, in 7 days of incubation. The production of HMG-CoA reductase inhibitors (simvastatin) occurs in the limiting condition of nitrogen and carbon sources, as important in the bioprocess. The results suggest that cassava husks can be used as a renewable and economical source in the production of HMG-CoA reductase inhibitors similar simvastatin by A. terreus UCP 0076, favoring the principles of circular bioeconomy and environmental sustainability.